Spatial variations in the effective elastic thickness of the lithosphere in Southeast Asia - Shi, X.; Kirby, Jon; Yu, C.; Jiménez-Díaz, A.; Zhao, J. (Elsevier BV, 2017)
As a proxy for long-term lithospheric strength, detailed information on lateral effective elastic thickness (Te) variations can aid in understanding the distribution pattern of surface deformation and its response to long-term forces. Here we present high-resolution maps of spatial variations of Te for the complex SE Asian region by analyzing the coherence of topography and Bouguer gravity anomaly data. We find that after considering the gravity deficit of less dense sediment, the recovered Te maps are more representative of the geology, particularly in elongated rift basins. The results show that the Te variation pattern in SE Asia, in general, agrees well with its tectonic provinces and major tectonic boundaries. The oceanic basins, the Indosinian suture zones between the Indochina and Sibumasu blocks, and the Makassar Strait are characterized by low Te, while moderate and high Te values are recovered in the Khorat plateau, West Burma, the Singapore Ridge, the Con Song Swell, Borneo, the northern Australian margin and the Molucca Sea. The Te pattern in the south Indonesian margin is complicated by the approach and collision of oceanic plateaus and seamounts with the fore-arc region. The heterogeneous strength features are consistent with the complex assemblage of different tectonic units, and significant deformation during Cenozoic tectonic events. In the Indochina Peninsula, the extruded displacement during the India-Eurasia collision might have been partitioned and absorbed by the combined mechanism of the extrusion and viscous tectonic models. As a result, the offshore displacements of the major strike-slip faults in the South China Sea are much smaller than originally assumed, thus having less effect on the development of the South China Sea than other mechanisms such as the slab pull of the proto-South China Sea. Since the displacement driven by the boundary tectonic forces has been greatly absorbed and decreased by subduction and deformation in the active margins and adjacent weak regions, the motion velocity of the interior regions is greatly lower than the boundary active margins, and they are largely free of seismicity and volcanism. Our results suggest that East Borneo might share a similar crustal basement, and represent a broad tectonic zone of the destroyed Meso-Tethys Ocean extending from West-Middle Java, through East Borneo to northern Borneo of the Sarawak and Sabah. The Indosinian zones between the Indochina and Sibumasu blocks might extend further southeastward across Billiton Island to offshore of southern Borneo, and the Singapore platform and SW Borneo might belong to the same block. The results also show that the internal load fraction F is high in the coastal area of South China, the northern margin of the South China Sea, and the coastal area of Indochina, which, in general, agrees with the distribution of a high-velocity lower crustal layer and Late Cenozoic basaltic rocks.